2021
DOI: 10.7717/peerj.10712
|View full text |Cite
|
Sign up to set email alerts
|

Rocks of different mineralogy show different temperature characteristics: implications for biodiversity on rocky seashores

Abstract: As some intertidal biota presently live near their upper tolerable thermal limits when emersed, predicted hotter temperatures and an increased frequency of extreme-heat events associated with global climate change may challenge the survival and persistence of such species. To predict the biological ramifications of climate change on rocky seashores, ecologists have collected baseline rock temperature data, which has shown substrate temperature is heterogenous in the rocky intertidal zone. A multitude of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 48 publications
(136 reference statements)
1
16
0
Order By: Relevance
“…While both seashores have similar oceanic and environmental conditions such as low wave exposure, a relatively flat shore slope, and are free from shading by cliffs, localised variations in wave splash and wind speed/direction may occur. Janetzki, Benkendorff & Fairweather (2021) showed that grey siltstone was consistently one of the hottest rock types sampled from this region, while quartzite was one of the coolest ( Appendix Fig. A1 ).…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…While both seashores have similar oceanic and environmental conditions such as low wave exposure, a relatively flat shore slope, and are free from shading by cliffs, localised variations in wave splash and wind speed/direction may occur. Janetzki, Benkendorff & Fairweather (2021) showed that grey siltstone was consistently one of the hottest rock types sampled from this region, while quartzite was one of the coolest ( Appendix Fig. A1 ).…”
Section: Methodsmentioning
confidence: 97%
“…Small boulders (maximum dimension ≤ 30 cm) represent one type of habitat that gastropods may seek refuge under during low tide. Janetzki, Benkendorff & Fairweather (2021) found that substrate temperature can be highly variable underneath boulders, with differences of up to 15.5 C between the hottest and coolest areas on a lower boulder surface. Moreover, the thermal quality of under-boulder habitats was influenced by lithology, with rock types differing in both maximum temperature and the qualitative patterns of temperature that developed across boulder surfaces when emersed (Janetzki, Benkendorff & Fairweather, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations